Pre-service teachers' preparedness to use ICT: A Western Australian perspective - Jin, H.; Pagram, J.; Cooper, Martin (2017)
This paper reports on an ongoing project being carried out at Edith Cowan University (ECU) in Western Australia examining ECU Education students’ ownership and use of Information and Communication Technology (ICT) since 2008. In particular the study to date has gathered information concerning students’ hardware ownership, self-perceived software skills, frequency of use of hardware and software, and access to Internet use. In the 2016 phase of this project, an online survey was designed and delivered via Qualtrics survey engine. 148 ECU Education students completed the survey. In comparison to the previous years results, the outcomes from the 2016 survey indicate a continuing positive trend in applying digital technology in education. The increase in the possession of laptops, smart phones and tablets and the way that devices are accessed suggests that more students are using portable devices and it is also the time for the universities to change their ICT policies and practice. This research has benefits and practical implications for lecturers and pre-service teachers through their integration of technology in their classroom teaching and learning more effectively and would have policy implications for administrators, course coordinators and future teacher education programs.